Evaluation of High-Alert Drug Storage in The Central Pharmacy of RSUD Ratu Zalecha Martapura: Evaluasi Penyimpanan Obat High Alert di Apotek Sentral RSUD Ratu Zalecha Martapura - Rosanti, Diah Aulia; Sari, Sri Oktaviani; Sari, Sindwi Rinanda; Mahendra, Rachul Ridho; Sandi, Dita Ayulia Dwi; Sari, Okta Muthia; Putra, Aditya Maulana Perdana; Rahmatullah, Satrio Wibowo; Jenah, Rina Astiyani; Hafizah, Noor (Universitas Tadulako, 2023)
Background: High-alert drugs require special attention when used because they can cause adverse reactions. High-alert drugs are classified into 3, namely, concentrated electrolytes, LASA, and cytostatics. Objectives: This study aimed to determine the evaluation of High-alert drug storage at the central pharmacy of Ratu Zalecha Martapura Hospital. Material and Methods: The research was conducted using a descriptive method, with observational data collection using an observation checklist sheet. The population and study sample took data on all High-alert medicines at the central pharmacy of Ratu Zalecha Martapura Hospital. Results: High alert drug storage was based on SOP, placed in a central pharmacy using the FIFO and FEFO methods, was placed in a separate place based on cytotoxic drug groups, electrolyte concentrates, and others. High alert drug storage according to storage temperature requirements for each drug (cold temperature and room temperature), was labeled